Control of mango anthracnose disease by using antagonistic bacteria - Asri, Muhamad Hafizzuddin (2016)
Mango anthracnose that caused by fungus Colletotrichum gloeosporioides can occurs at any stages of fruit growth and always related with latent infection of the fruits. Fungicides are frequently used to control the disease but the chemical residues can give harm to human health, pollute the environment, and prolong application of fungicides can cause the fungus to develop resistance. Three antagonistic bacteria namely UMB 20 (Pseudomonas fluorescens), KMB 25 (Pseudomonas aeruginosa), and B 40 (Bacillus subtilis) were screened for their potential against C. gloeosporioides. Based on the dual culture test, all the bacterial isolates are significantly inhibited the growth of C. gloeosporioides with their PIRG values of 20.59% (UMB 20), 47.06% (KMB 25), and 45.23% (B 40). All bacterial isolates produced diffusible metabolites as indicated by the cell-free supernatant method, with the PIRG values of 11.430% (UMB 20), 37.143% (KMB 25), and 42.857% (B 40) inhibition of radial growth. From both methods, it showed that KMB 25 and B 40 are more effective in suppressing the fungus using PDA medium. The mechanism involve in these inhibitions is more related to production of diffusible metabolites by the bacterial isolates that inhibited the growth of C. gloeosporioides.